Visualisasi Pentatalaksanaan Rekam Medis di Masa Pandemi Covid-19 pada Pembelajaran Praktikum Laboratorium Melalui Media Video Tutorial - Subinarto Subinarto; Isnaini Qoriatul Fadhilah; Puput Sugiarto (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
The Covid-19 pandemic has had an impact on health services in Indonesia. Health workers, especially PMIK, must pay attention to the procedures for handling Covid-19 in providing services to patients. Medical record management procedures need to be taught to students in order to gain knowledge and understanding of medical record management during the Covid-19 pandemic. Visualization of the management of medical records during the Covid-19 pandemic is needed for students in video tutorial media. The purpose of this research is to develop visualization in video tutorial media about the management of medical records during the Covid-19 pandemic in laboratory practicum learning. The study used the research and development method which was carried out in the manual medical record laboratory of Poltekkes Kemenkes Semarang from August to December 2021. The stages in this study began with a needs analysis through FGD, followed by the stages of making video tutorials, testing validity, and ending at the trial stage. . The results of the study obtained visualization in the form of video tutorials which have been declared very valid in the material test by 85% and media testing by 81% by experts. Practicality tests on videos that were conducted on students obtained practical results with a value of 78% so that they were able to provide visualization to students on the management of medical records during the Covid-19 pandemic. It is necessary to measure the effectiveness of video tutorials in increasing students' knowledge and skills regarding the management of medical records during the Covid-19 pandemic.